An assessment of mercury in estuarine sediment and tissue in Southern New Jersey using public domain data. Issue 1 (15th June 2016) - Ng, Kara; Szabo, Zoltan; Reilly, Pamela A.; Barringer, Julia L.; Smalling, Kelly L.
Abstract: Mercury (Hg) is considered a contaminant of global concern for coastal environments due to its toxicity, widespread occurrence in sediment, and bioaccumulation in tissue. Coastal New Jersey, USA, is characterized by shallow bays and wetlands that provide critical habitat for wildlife but share space with expanding urban landscapes. This study was designed as an assessment of the magnitude and distribution of Hg in coastal New Jersey sediments and critical species using publicly available data to highlight potential data gaps. Mercury concentrations in estuary sediments can exceed 2 μg/g and correlate with concentrations of other metals. Based on existing data, the concentrations of Hg in mussels in southern New Jersey are comparable to those observed in other urbanized Atlantic Coast estuaries. Lack of methylmercury data for sediments, other media, and tissues are data gaps needing to be filled for a clearer understanding of the impacts of Hg inputs to the ecosystem. Highlights: Summary of Hg in estuarine sediment and biota from New Jersey identify data gaps. Hg concentrations in sediments exceed sediment quality guidelines at some sites. Hg in sediments and mussels is similar to other urbanized Atlantic estuaries. Lack of methylmercury data for sediment, water, and biota are important data gaps.